Pre-entry academic and non-academic factors influencing teacher education students’ first-year experience and academic performance - Pather, Subethra (Cape Peninsula University of Technology, 2015)
The research question that guided this doctoral study is: How do pre-entry academic and non-academic factors influence teacher education students’ first-year experience and academic performance? The study was designed within the qualitative research paradigm and employed a case study strategy to collect both quantitative and qualitative data. The quantitative approach included a questionnaire that was completed by 195 respondents. The qualitative data was obtained from one-on-one and focus-group interviews with eight participants that were purposively selected. The conceptual framework developed for this enquiry took into consideration the significance of student diversity in understanding first-year experience and thus employed concepts from two sociological models, Tinto’s (1975; 1993) integration model (social and academic integration) and Bourdieu’s (1984; 1990) theoretical tools of capital, habitus and field. Six key themes emerged from the data: determination, self-reliance, fitting-in, out-of-habitus experience, positioning oneself to succeed and challenges. The unequal distribution of economic, social and cultural capital created disparities between students’ habitus and schooling experiences which influenced the way they integrated into their first year at university. The study revealed that more mature students than school-leavers and gap-students are entering higher education. Further, the majority of first-year students are unable to fund their studies and source external funding or engage in part-time employment. Students pursued financial aid before focusing on academic activities. Engagement in the social domain remained marginal. Students’ determination to change their economic circumstances was the primary factor that influenced their attitudes and actions at university. Higher education needs to consider student diversity, financial constraints of disadvantaged students, first-year curriculum planning and delivery, and the high cost of university studies. It needs to move away from viewing entering students from a deficit model, to capitalise on their qualities of determination, optimism, enthusiasm and openness to learning, thereby creating an inclusive first-year experience that could encourage retention and student success.
Thesis (DEd)--Cape Peninsula University of Technology, 2015
Keywords: Pre-entry academic factors; Non-academic factors; Teacher education students; First-year experience; Academic performance